The Implicit Costs of Motherhood over the Lifecycle: Cross‐Cohort Evidence from Administrative Longitudinal Data. (20th October 2017) - Neumeier, Christian; Sørensen, Todd; Webber, Douglas
Abstract : It is well known that the explicit costs of raising a child have grown over the past several decades. Less well understood are the implicit costs of having a child, and how they have changed over time. In this article, we are the first to examine the evolution of the implicit costs of motherhood over the lifecycle and across generations using high quality administrative data. We estimate that the lifetime labor market income gap between mothers and women who never have children (never‐mothers) decreases from around $350, 000 to $280, 000 between women born in the late 1940s and late 1960s. Gaps tend to increase monotonically over the lifecycle, and decrease monotonically between cohorts. Our evidence suggests that changes in the gaps are caused by changing labor force participation rates.